PENGARUH MODEL PEMBELAJARAN COLLABORATIVE PROBLEM SOLVING BERBANTUAN DESMOS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Lubis, Adinda Mutiara Rahma; Saragih, Sri Rahma Dewi (MES: Journal of Mathematics Education and Science, 2026)
The purpose of this study was to determine whether there was an effect of the implementation of the Collaborative Problem-Solving learning model assisted by Desmos on students’ mathematical problem-solving ability in quadratic function material for class X at SMA Negeri 1 Aek Kuasan in the 2025/2026 academic year. This research used a quasi-experimental method with a two-group pretest-posttest design. The population in this study consisted of all class X students, which were divided into six classes. The sample of this study consisted of two classes, namely class X-2 and class X-3, selected using cluster random sampling. Class X-2 was used as the experimental class using the Collaborative Problem-Solving learning model assisted by Desmos, while class X-3 was used as the control class using the direct learning model assisted by Desmos. After the learning process was completed, the posttest results showed that the average score of the experimental class was 80.027, while the control class was 67.583. The t-test result showed that t_hitung=6,722>t_tabel=1,994, therefore H_0 was rejected and H_a was accepted. Thus, it can be concluded that there was an effect of the Collaborative Problem-Solving learning model assisted by Desmos on students’ mathematical problem-solving ability in quadratic function material for class X at SMA Negeri 1 Aek Kuasan in the 2025/2026 academic year.